Analisis teoritis tentang hubungan antara budaya organisasi dan kinerja karyawan - Najwa Novia Ulfa Samosir; Tengku Darmansah; Erfiani Lubis; Ifra Mayanti Harahap; M. Syahan (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
Organizational culture is the foundation that shapes thought patterns, behavior and interactions within the organization, so it plays an important role in influencing employee performance. This research aims to analyze the theoretical relationship between organizational culture and employee performance using the literature study method. Literature searches were carried out on various sources such as books, journals and relevant research reports. Findings show that a positive organizational culture, with values ​​such as trust, cooperation, and innovation, can significantly improve employee performance through higher motivation and job satisfaction. On the other hand, an unsupportive organizational culture can hinder employee potential, give rise to conflict and reduce productivity. This research concludes that effective management of organizational culture is the key to creating a work environment that is conducive to individual growth and achieving organizational goals. These results provide a theoretical basis for the development of organizational culture management strategies.